2020
DOI: 10.1177/2050640620925968
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide accelerates colonic transit in people with type 1 diabetes and polyneuropathy: A randomised, double‐blind, placebo‐controlled trial

Abstract: Background Glucagon-like peptide-1 receptor agonists, such as liraglutide, reduce hyperglycaemia and induce weight loss and are used as a treatment in diabetes. However, common adverse effects include nausea, loss of appetite and prolonged gastric emptying. It is not known whether these changes are centrally generated or if liraglutide alters the enteric motility. Objective To investigate the effects of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…In one study, osmotic diarrhea occurred 8 h after infusion of GLP-1 peptide (47), and GLP-1RAs have been shown to reduce intestinal uptake of glucose and lipids (48,49). Also, in patients with type 1 diabetes, liraglutide reduced colon transit time (50). So, hypothetically, semaglutide could induce diarrhea by altering nutrient absorption or intestinal motility.…”
Section: Gastrointestinal (Gi) Adverse Effectsmentioning
confidence: 99%
“…In one study, osmotic diarrhea occurred 8 h after infusion of GLP-1 peptide (47), and GLP-1RAs have been shown to reduce intestinal uptake of glucose and lipids (48,49). Also, in patients with type 1 diabetes, liraglutide reduced colon transit time (50). So, hypothetically, semaglutide could induce diarrhea by altering nutrient absorption or intestinal motility.…”
Section: Gastrointestinal (Gi) Adverse Effectsmentioning
confidence: 99%
“…In contrast, the impact of GLP-1 on colonic motility was opposite compared with other intestinal segments. A recent randomized and placebo-controlled trial confirmed that liraglutide could accelerate large bowel transit and decreases the motility index in type 1 diabetes and polyneuropathy, which may indicate better coordination of propulsive motility ( Wegeberg et al, 2020 ). Endogenous GLP-1 has a modest effect on gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-known hypoglycemic effect of GLP-1 RAs, increasing evidence showed that GLP-1 RAs also profoundly affect the gastrointestinal motor system ( Marathe et al, 2011 ). In contrast, the impact of GLP-1 RAs on gut motility may vary with the change in intestinal segments ( Nauck et al, 1997 ; Thazhath et al, 2016 ; Wegeberg et al, 2020 ). Endogenous GLP-1 is rapidly degraded by the dipeptidyl peptidase-4 (DPP-4), resulting in a short half-life.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of liraglutide, a glucagon-like peptide-1 receptor agonist, which is employed to reduce hyperglycemia and to control food intake [ 113 ]. Liraglutide has been indeed recently reported, other than to ameliorate the function of the ENS, leading to the normalization of colonic function in people with type 1 diabetes [ 114 ], to improve NOS activity and increase NO production [ 115 ].…”
Section: No and Possible Therapeutic Strategiesmentioning
confidence: 99%